The Long-Term Settlement Deformation Automatic Monitoring System for the Chinese High-Speed Railway - Xu Wang; Liangqin Wu; Yi Zhou; Yanru Wang (Shock and Vibration)
The Beijing-Shanghai high-speed railway is one of the milestones of China’s high-speed railway development and its security plays a significant role in China’s economic and social development. However, the evaluation methods used for large-scale security operations and important infrastructure systems, such as the high-speed railways, are discrete and nonlinear; thus they cannot issue emergency warnings in a timely manner. The emergence of optical fiber sensing technology can solve this problem. This technology has progressed rapidly in its application to the monitoring of railway security and it has attracted much attention within the industry. This study considers the newly built passenger railway line between Shijiazhuang and Jinan as an example. The web-based, all-in-one fiber Bragg grating static level is described as well as a set of online monitoring systems, which is automated, real-time, remote, visual, and adaptable to the standards of the Beijing-Shanghai high-speed railway. According to our theoretical analysis, the planned automated monitoring of settlement deformation for the Beijing-Shanghai high-speed railway and the real-time analysis and calculation of monitoring data can ensure the operational security of this section of China’s high-speed railway system.